Feeding of high producing dairy cows according to rumen undegradable protein requirements in grass silage based diet - Setälä, Jouko; Syrjälä-Qvist, Liisa; Poutiainen, Esko (Agricultural and Food Science, 1984)
The experiment was performed with 21 Ayshire cows 4—16 weeks post calving. Cows received restricted amounts (according to calculated intake) of unwilted grass silage, preserved with a mixture of acetic acid and formalin and two kilograms of hay/cow/day. A concentrate mixture including dried and propionic acid treated barley and oats together with a mineral-vitamin mixture was given 0.3 kg/kg FCM. During the standardization period (2 weeks) protein feeding of the cows was performed according to the DCP requirements and the diet was supplemented with soybean meal if necessary. For the adaptation period (3 weeks) and the comparison period (8 weeks) the cows were divided in 3 equal groups of 7 cows (G1, G2, G3). G 1 had no protein supplement in the diet. The diets of G 2 and G 3 were supplemented correspondingly either with rapeseed meal or formaldehyde treated urea on the basis of the UDP (undegradable feed protein) requirements (G2) and the DCP requirements (G3) of the cows. Efficient protein degradabilities in the total diets during the comparison period varied from 77 to 85 % when the determinations were made with the nylon bag technique. The highest degradabilities were found for the diet of G3 and the lowest for G 2. Significantly (P < 0.05, 0.01) the highest yields of FCM and milk protein were recorded for Group2 (G2) in which the cows received protein supplement according to their UDP requirements. Using a factorial approach, conversion of protein absorbable in the small intestine to milk protein was calculated to be 66.5 ± 0.8 % when all the cows in three groups were taken into account.